(untitled) (JÓVENES EN LA CIENCIA, 2025)
This paper examines the transformative impact of artificial intelligence on education, with particular emphasis on its application in multimedia e-learning courses. The integration of artificial intelligence into the design of electronic multimedia e-learning courses creates new possibilities for personalized learning and significantly enhances the overall effectiveness of the educational process. AI-driven solutions promote deeper understanding and foster greater learner engagement. The inclusion of interactive, AI-powered components provides ongoing support and broadens opportunities for autonomous learning. As a result, artificial intelligence emerges as a key instrument in the development of innovative educational environments that meet the evolving needs of a contemporary society. The study also addresses ethical issues and data security risks related to AI use.